1997
DOI: 10.2337/diacare.20.4.537
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diet and Exercise in Preventing NIDDM in People With Impaired Glucose Tolerance: The Da Qing IGT and Diabetes Study

Abstract: Diet and/or exercise interventions led to a significant decrease in the incidence of diabetes over a 6-year period among those with IGT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

79
2,400
10
120

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,633 publications
(2,659 citation statements)
references
References 0 publications
79
2,400
10
120
Order By: Relevance
“…Among 577 subjects with IGT in Da Qing study (Pan et al, 1997), exercise interventions, dietary interventions or both resulted in a decreased of 42-46% in the rate of progression from IGT to DM during the 6-y follow-up. The Finnish Diabetes Prevention Program reported that diet (low in saturated and trans fat, high in fiber) and lifestyle modification (small reduction (less than 4.5 kg) in weight and regular moderate exercise) reduced the incidence of type II DM by 58% during 3.2 y of follow-up among 522 middle-aged, overweight subjects with IGT (Tuomilehto et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 577 subjects with IGT in Da Qing study (Pan et al, 1997), exercise interventions, dietary interventions or both resulted in a decreased of 42-46% in the rate of progression from IGT to DM during the 6-y follow-up. The Finnish Diabetes Prevention Program reported that diet (low in saturated and trans fat, high in fiber) and lifestyle modification (small reduction (less than 4.5 kg) in weight and regular moderate exercise) reduced the incidence of type II DM by 58% during 3.2 y of follow-up among 522 middle-aged, overweight subjects with IGT (Tuomilehto et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting about some results of the primary prevention of type II DM (Pan et al, 1997;Tuomilehto et al, 2001;Diabetes Prevention Program Research Group, 2002;Hu et al, 2002). Among 577 subjects with IGT in Da Qing study (Pan et al, 1997), exercise interventions, dietary interventions or both resulted in a decreased of 42-46% in the rate of progression from IGT to DM during the 6-y follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence on type 2 diabetes prevention strategies is extensive, 1,[14][15][16] and currently, clinicians in the United States seeking to help patients reduce their diabetes risk recommend lifestyle change and monitor weight, fasting glucose, and/or HbA1c levels periodically. Among persons undergoing lifestyle change, we show that greater weight loss at 6 months predicts decreased 3-year diabetes risk in a graded fashion and that achievement of fasting glucose <100 mg/dl at 6 months is beneficial regardless of weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention studies have demonstrated that lifestyle changes including increased physical activity can reduce the incidence of diabetes among individuals with impaired glucose tolerance (IGT) [1][2][3]. However, it is unknown whether these results can be extrapolated to individuals with isolated impaired fasting glucose (i-IFG) [4].…”
Section: Introductionmentioning
confidence: 99%